Bridging the Gap in Traditional PIVC Placement: An Evaluation of Operation STICK Vascular Access Outcomes - Mielke N; Xing Y; Gibson SM; DiLoreto E; Bahl A (Dove Medical Press, 2023)
Nicholas Mielke,1 Yuying Xing,2 Steven Matthew Gibson,3 Emily DiLoreto,4 Amit Bahl4 1Department of Medicine, Creighton University School of Medicine, Omaha, NE, USA; 2Corewell Health Research Institute, Royal Oak, MI, USA; 3Vascular Access Consulting, Henderson, KY, USA; 4Department of Emergency Medicine, Corewell Health William Beaumont University Hospital, Royal Oak, MI, USACorrespondence: Amit Bahl, Department of Emergency Medicine, Corewell Health William Beaumont University Hospital, 3601 13 Mile Road, Royal Oak, MI, 48073, USA, Email amit.bahl@corewellhealth.orgObjective: Education and training is core to improving peripheral intravenous access outcomes. This study aimed to show that a vascular access training program (Operation STICK) in the emergency department (ED) improves the outcomes of traditionally placed peripheral intravenous catheters (PIVC).Methods: This was a pre-post quasi-experimental study of traditionally placed PIVCs at a large ED in southeastern Michigan, United States. A control group (non-OSTICK) was compared to an experimental group (OSTICK) using a 3:1 propensity score matched analysis. Groups were comprised of ED patients with traditional PIVC placements in two separate six-month periods: non-OSTICK PIVCs from April to September 2021 and OSTICK PIVCs (placed by an OSTICK graduate) from October 2022 to March 2023. The primary outcome was PIVC functionality. The secondary outcome was adherence to best practices.Results: A total of 6512 PIVCs were included in the study; 4884 (75.0%) were in the non-OSTICK group, while 1628 (25.0%) were in the OSTICK group. 68.1% of OSTICK PIVCs and 59.7% of non-OSTICK PIVCs were placed by ED technicians (p < 0.001). 91.3% of OSTICK PIVCs were placed on the first attempt, and 98.5% were placed within two attempts. A subgroup analysis of admitted patients (2540 PIVCs; 553 (21.8%) OSTICK-trained and 1987 (78.2%) non-OSTICK-trained) revealed 87.6% of OSTICK PIVCs and 80.3% of non-OSTICK PIVCs were 20 gauge (p < 0.001). The median proportion of dwell time to hospital length of stay was 94% for OSTICK PIVCs, compared to 88% for non-OSTICK PIVCs (p < 0.001).Conclusion: This study underscores the value of education and training in enhancing vascular access outcomes. Implementing Operation STICK, a comprehensive vascular access training program, at a large ED has led to high first-stick success, adherence to best practice recommendations for site and device selection, and improved PIVC functionality for traditionally placed catheters.Keywords: peripheral intravenous catheter, venous access, vascular access score, traditional insertion, operation stick, palpation method